Improvement Of Structure And Body Of Three Wheeler Vehicle - Bekele, Eromo (My University, 2017)
Three wheeler vehicles are used as one of the major public transportation systems in Ethiopia society. They have played very important role in a short distance transport system in Ethiopia especially in city and town. It is important to evaluate the current strength of three wheeler vehicle depending on their load carrying capacity, service and use. The purpose of this thesis is to improve the design of body and structure of three wheeler vehicles in order to bring significant change in their overall activity. To fulfill the objectives of this study the following main activities were performed. CAD model was prepared by using CATIA V5R19 software, structure analysis was done by using finite element analysis (FEA) with ANSYS 16.0 software. Also for impact analysis such as frontal, rear, side and rollover static impact analysis finite element analysis software was used and aerodynamic drag analysis was done by using CFD software. The current work of the thesis was made by the important parameters such as strength, performance, weight and safety. Designing the overall body shape and structure improve vehicle stability and handling. The modified structure increases the strength of vehicle and the rollover static crash simulation which makes strong roof structure during collision. This rollover impact simulation is used to bring great change in order to protect occupants from rollover accidents. Also a modified the outer surface of the vehicle aerodynamically in order to reduce the effect of drag force which in turn results in reduction of fuel consumption. The models were entirely designed using the software CATIA V5R19. Simulation of model dimensions 2625 x 1300 x 1710 mm was conducted using CFD software Fluent16.0 in order to reduce the drag force. Computation fluid dynamics (CFD) method was important to analyze the variation of aerodynamic effect on the models with the change of body shape. From the study, it was found that 24.6% of the total drag of the original (Model-1) was reduced on the model-2 that is equivalent to 4.93 KW of an engine brake power at 60 km/h in speed. Also 8.1% of fuel can be saved for the every 60 Km/h.